Transcriptome analysis of gills reveal the key metabolism-related genes and pathways response to ammonia nitrogen stress in Scylla paramamosain - Chaoyue Wang; Xiao Liu; Jie Zhou; Sixiang Wang; Xia Zheng; Zehao Li; Yuanyuan Fu; Zhongwen Jin; Lei Liu (Frontiers in Marine Science)
Ammonia nitrogen is highly toxic to crustaceans; however, studies investigating the molecular mechanisms underlying its metabolism and excretion in these organisms remain scarce. The present study aims to identify key genes and investigate the molecular mechanisms in response to ammonia nitrogen using RNA sequencing in Scylla paramamosain, a key economic crab species in Asia that is subjected to ammonia nitrogen stress in aquaculture. The median lethal concentrations (LC50) of ammonia nitrogen exposure were determined as 325.4 mg/L for 24 hours, 253.7 mg/L for 48 hours, and 198.2 mg/L for 72 hours. Subsequently, crabs were exposed to 325.13 mg/L NH4Cl for durations of 24, 48, and 96 hours, followed by transcriptome sequencing to identify differentially expressed genes (DEGs) related to ammonia nitrogen metabolism in the anterior and posterior gills of Scylla paramamosain. Ammonia nitrogen stress caused significant damage to the morphology and structure of the gills, with prolonged exposure leading to further damage, including cellular vacuolization and narrowing of the gill hemolymph chambers. A total of 184.66 Gb of clean data and 36,439 DEGs were obtained, including 7,880 DEGs in the anterior gill and 28,559 DEGs in the posterior gill, which were implicated in the regulation of ammonia nitrogen metabolism-related pathways. KEGG enrichment analysis revealed that ammonia nitrogen stress induced changes in the expression of metabolism- and immune-related genes. Following ammonia nitrogen stress, the expression of ammonia nitrogen metabolism-related genes (punA, XDH, rocF, allB) in the anterior gill was upregulated, whereas the expression of genes in the posterior gill (GART, rocF, alc) was downregulated. These results indicate that ammonia nitrogen stress enhances ammonia nitrogen metabolism in the anterior gill, while inhibiting this process in the posterior gill. The expression of immune-related genes (Hsp10, Hsp70, Hsp90, CTL) in both the anterior and posterior gills was downregulated following ammonia nitrogen stress, suggesting that ammonia nitrogen stress diminished the organism’s immune capacity. These findings provide a theoretical foundation for understanding the molecular mechanisms regulating ammonia nitrogen metabolism and for improving the artificial culture of Scylla paramamosain.